Enteric fever and the diagnostic tools: defining the accuracy - Diwaker, Amita; Tiwari, Ashutosh; Jain, Shubham; Rupali, Kumari Astha; Ram, Jitendra; Singh, Samer; Kishore, Dhiraj (Frontiers in Bacteriology, 2024)
Enteric fever is widespread in many regions of developing countries. Despite low sensitivity, blood culture remains the gold standard diagnostic test for enteric fever. Diagnostic tests like Widal lack the desired specificity; hence, patients are overtreated many times. Inaccessibility to proper medical care in developing countries further poses a challenge to diagnosis by these conventional methods, promoting the needless intake of over-the-counter drugs by people. Though rapid kit-based tests are available, the reliability of these diagnostic tests in terms of specificity and sensitivity is quite variable. We aimed to validate the reliability of Typhipoint EIA (ELISA-based test) against blood clot nested PCR for enteric fever, as a gold standard, in view of the reported variable culture yield by calculating sensitivity, specificity, and likelihood ratio. A total of 100 patients were included in the study out of 152 patients screened, based on the inclusion criteria. The clinical profile of provisional enteric fever was recorded along with the amplification of the DNA fragment of flagellin (H1-d), and the stkG gene of Salmonella typhi and Salmonella paratyphi A, respectively, by nested PCR performed on blood clots, urine, and stool samples. Further validation of ELISA-based test, i.e., Typhipoint EIA, was done considering nested PCR as a gold standard. The control group consisted of 40 healthy subjects. Nested PCR of the blood clots showed 84% positivity. Total culture positivity was found in 89 samples (combined), and among all samples for culture, clot culture was positive in 52 (52%), urine culture in 5 (5%), and stool culture in 32 (32%) cases, respectively. Total Typhipoint EIA IgM positive cases were 83 (83%). The validation of Typhipoint EIA IgM showed 92.9% sensitivity and 68.8% specificity against blood clot PCR for Salmonella typhi. The Typhipoint EIA test for the diagnosis of enteric fever is quite sensitive as well as specific. It may be advised that 2-3 specific antigens of S. typhi should be spotted on the test kit for a satisfactory level of diagnosis of enteric fever in field conditions. This will help achieve the desired accuracy of the rapid test to avoid unnecessary antimicrobial therapy and costly investigations.